TEACHING SOCIAL WORK VALUES BY MEANS OF SOCRATIC QUESTIONING - Ferreira, Sandra; Ferreira, Regardt Jacobus (Social Work/Maatskaplike Werk, 2015)
This article provides an outline of the challenging process of teaching, acquiring and internalising social work values, which form an important aspect on which ultimate ethical decision making with clients rests. The supposition is that treating clients impartially, reasonably and justly is dependent on students’ understanding and awareness of their thinking about their thinking. Becoming a strong-sense thinker implies a cultivated disposition of mind without privileging one’s own views and being skilled in the ability to formulate a disciplined line of questioning. The use of Socratic Questioning (SQ) as a form of professional socialisation to teaching professional values may enable students to eventually develop into reflective practitioners.